Integration of additive-free Ni–Cu–Zn ferrite layers into LTCC multilayer modules. Issue 8 (July 2016) - Hesse, J.; Naghib-zadeh, H.; Rabe, T.; Töpfer, J.
Abstract: The sintering behavior of sub-micron Ni0.30 Cu0.20 Zn0.52 Fe1.98 O3.99 ferrite with and without Bi2 O3 addition was studied. Ferrites with 0.5 wt% Bi2 O3 exhibit enhanced shrinkage at T < 900 °C with significant grain growth. Additive-free ferrite powders also sinter to high density at 900 °C, however, grain growth is very limited. Both ferrites exhibit a permeability of μ = 400–450. Multilayers consisting of ferrite and low-k dielectric LTCC layers were prepared by co-firing at 900–915 °C. The shrinkage and thermal expansion characteristics of ferrite and LTCC tapes are similar. However, the permeability of integrated ferrite layers, made from ferrite tapes with Bi2 O3 additive, significantly drops after co-firing with LTCC layers compared to separately fired monolithic ferrite multilayers. Contrarily, the permeability of integrated, Bi2 O3 -free ferrite layers, co-fired with dielectric tapes, is identical to that of monolithic ferrite multilayers. This finding is an important step toward ferrite integration into complex LTCC multilayer architectures.